2013
DOI: 10.1002/pbc.24485
|View full text |Cite
|
Sign up to set email alerts
|

Prompt administration of antibiotics is associated with improved outcomes in febrile neutropenia in children with cancer

Abstract: Background Time‐to‐antibiotic (TTA) administration is a widely used quality‐of‐care measure for children with cancer and febrile neutropenia (FN). We sought to determine whether TTA is associated with outcomes of FN. Procedure A single‐center, retrospective cohort study was conducted of 1,628 FN admissions from 653 patients from 2001 to 2009. Outcome variables included (1) an adverse event (AE) composite of in‐hospital mortality, pediatric intensive care unit (PICU) admission within 24 hours of presentation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 35 publications
4
83
3
6
Order By: Relevance
“…[11,15,16] A recently published study reported 11.1% composite AE outcome in FN patients with in-hospital mortality of (0.7%), PICU admission (4.7%), and fluid resuscitation > 40 ml/kg in (10.1%). [17] Out data also showed that severe myelosuppression was associated with composite AE outcome as patients with more severe neutropenia and thrombocytopenia have a higher risk for AE [13,21]. A diagnosis of sepsis or bacteremia conferred a 2.3-fold increase in the risk (13% vs. 29%; p=0.05) of composite AE.…”
Section: Discussionmentioning
confidence: 93%
“…[11,15,16] A recently published study reported 11.1% composite AE outcome in FN patients with in-hospital mortality of (0.7%), PICU admission (4.7%), and fluid resuscitation > 40 ml/kg in (10.1%). [17] Out data also showed that severe myelosuppression was associated with composite AE outcome as patients with more severe neutropenia and thrombocytopenia have a higher risk for AE [13,21]. A diagnosis of sepsis or bacteremia conferred a 2.3-fold increase in the risk (13% vs. 29%; p=0.05) of composite AE.…”
Section: Discussionmentioning
confidence: 93%
“…Esto tiene una importancia enorme, ya que el retraso para la administración de los antimicrobianos se ha correlacionado con peor pronós-tico, mientras que el inicio rápido se ha relacionado con mejor pronóstico 9,10 . Sin embargo, a pesar de esfuerzos constantes para cumplir con esta cuota, se ha visto un alargamiento progresivo del tiempo para la administración de los antimicrobianos, tanto así que > 50% de los departamentos de emergencias en E.U.A.…”
Section: Importancia Del Tiempo Para Inicio Del Tratamientounclassified
“…Afortunadamente, está bien establecido que el tratamiento antimicrobiano oportuno disminuye la mortalidad por una infección bacteriana seria de forma considerable 9 . Por otro lado, el retraso para la administración de antimicrobianos se ha correlacionado con peor pronóstico 10 . Por estas razones, es de suma importancia que el mé-dico conozca bien el manejo del niño con cáncer que se presenta con fiebre al servicio de emergencias y en el que se documenta neutropenia en el hemograma.…”
Section: Introductionunclassified
“…[1] The signs and symptoms of inflammation and infection may be absent in these patients. Early empiric therapy [2][3][4] is imperative and may directly affect the clinical outcome during and after the illness. The time duration taken to start the patient on antibiotics has a correlation with the outcome.…”
Section: Introductionmentioning
confidence: 99%